1986
DOI: 10.1007/bf00377336
|View full text |Cite
|
Sign up to set email alerts
|

Population cycles caused by overcompensating density-dependence in an annual plant

Abstract: We analyse demographic data from a seven-year study of the annual crucifer Erophila verna which showed two-year cycles of abundance in the field. The unusual behaviour of this population is shown to be the consequence of overcompensating density-dependence. Very local differences in germination succes between plots can account for observed differences in their population dynamics over the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 5 publications
2
40
1
Order By: Relevance
“…One source of population fluctuations is a high intrinsic rate of growth coupled with overcompensating density dependence. Models of populations with discrete generations exhibiting these characteristics can exhibit complex dynamical patterns (May, 1975;Stone, 1993;Getz, 1996) that have been observed in insect populations (Turchin and Taylor, 1992;Costantino et al, 1997;Cushing et al, 1998), annual plant populations (Symonides et al, 1986), and vertebrate populations (Grenfell et al, 1992;Turchin and Taylor, 1992;Turchin, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…One source of population fluctuations is a high intrinsic rate of growth coupled with overcompensating density dependence. Models of populations with discrete generations exhibiting these characteristics can exhibit complex dynamical patterns (May, 1975;Stone, 1993;Getz, 1996) that have been observed in insect populations (Turchin and Taylor, 1992;Costantino et al, 1997;Cushing et al, 1998), annual plant populations (Symonides et al, 1986), and vertebrate populations (Grenfell et al, 1992;Turchin and Taylor, 1992;Turchin, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…[7,16]). (8) As is well known [17,18], accumulated litter is subject to decomposition. Without it the soil would be totally covered by dead biomass, preventing any germination.…”
Section: Modelmentioning
confidence: 99%
“…Cycles in plant population dynamics have been debated since a long time [15,18,21] and the role of litter in producing such cycles has been conjectured [17,18]. It is believed [15] that deviations from a stationary state, like oscillations or chaos, come from lagged density dependence.…”
Section: Oscillationsmentioning
confidence: 99%
“…While external factors cause major fluctuations in plant populations, plants also face unpredictable fluctuations in the abundance of competing species and morphs of the conspecifics. It has been suggested that plant populations may fluctuate due to their intrinsically unstable dynamics (Symonides et al, 1986;Silvertown, 1991;Silvertown & Lovett Doust, 1993;Gonzales-Andujar & Hughes, 2000; but see Rees & Crawley, 1989, 1991 and of all life history strategies annuals show the greatest fluctuations (Silvertown, 1991). A seed bank has a ''storage effect'' (Chesson, 1986), which enables the renewal of the banker morph even after years of complete reproductive failure.…”
Section: Introductionmentioning
confidence: 98%